G240 Coordinating care: the multifaceted role of the key worker in children's cancer care. (7th April 2014) - Martins, A; Aldiss, S; Taylor, R; Gibson, F
Abstract : Aims: The cancer journey is complex and involves care interventions from various multisite professionals. There is a need for effective co-ordination between those professionals involved in the care of children and young people. The key worker role (i.e., named individual) has been identified to provide this service. Little is known however about how this role is being implemented, what are the obstacles and facilitators for an effective coordination of care and the impact it has on services and on the work between the different professionals involved in the patient's care. This first phase of our study aims to describe post-holders' perceptions of the specialist key worker role working within and out with children's cancer units across the UK. Methods: A group of children's oncology specialist nurses across 18 Principal Treatment Centres are currently funded as a key worker for families. This study used a qualitative approach to explore their views of the role. Eighteen individual semi-structured interviews and one focus group (n = 12) were conducted. Results: Thematic analysis revealed three main themes -model of care, needs assessment and perceptions of the role. This in-depth exploration of key workers' role, their caseload, and the context of their practice contributed to the identification of different ' models of care '. Variations were identified in nurses' management leadership role in ensuring the coordination, communication and planning of the team work; nurses supportive role in the provision of expert advice and guidance to other members of the team and impact on the services. A holistic approach to families' needs has been adopted. Coordination of care, support and information were the main aspects of the role identified by professionals. The use of the 'key worker' term varied and there were mixed attitudes towards the term. Conclusion: Data has revealed complexity and variation in the role, showing the realities of how it works in practice and the challenges it entails. Care coordination is perceived as important, but less than straightforward. This presentation will present a perspective on the key worker role that is fundamental to the experience of patients following their cancer diagnosis.